2018
DOI: 10.1093/asj/sjy188
|View full text |Cite
|
Sign up to set email alerts
|

The Excision of the Buccal Fat Pad for Cheek Refinement: Volumetric Considerations

Abstract: Buccal fat pad removal is an effective technique for refining the facial silhouette that should be reserved only for patients with increased buccal fat pad volume. Removal of only the excessive portion of the fat pad is important because this structure provides significant volume in the midface that can be difficult to restore once aging takes its toll on the surrounding soft and bony tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 43 publications
0
45
0
10
Order By: Relevance
“…Finally, 3 case series studies ( 5 , 6 , 33 ) and 1 RCT ( 34 ) met the inclusion criteria and were selected for qualitative and quantitative synthesis (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, 3 case series studies ( 5 , 6 , 33 ) and 1 RCT ( 34 ) met the inclusion criteria and were selected for qualitative and quantitative synthesis (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…All 3 observational studies ( 5 , 6 , 33 ) were assessed by the adapted NOS. The mean NOS score was 5 (Range: 3 to 8), being the domain “Selection” the highest ranked and the “Comparability” the lowest ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 3 One ultrasonographic study estimated the volume of buccal fat per cheek to be 11.67 mL and reported that the average amount of fat removed was 2.74 mL. 4 Although the procedure is relatively simple, a challenge surgeons face is estimating the amount of fat removed and ensuring that equal amounts of fat are removed from both cheeks. Failure to do so may lead to facial asymmetry.…”
mentioning
confidence: 99%